Entablar una demanda civil: modalidades y finalidades de una causa por “cobro de pesos” (Copiapó, Chile, mediados del siglo XIX) - Pauline Bilot (Centre de Recherches sur les Mondes Américains, 2012)
Through the analysis of a civil proceeding from Copiapo's juzgado de letras, this paper explore some aspects of Chilean mid-nineteenth century civil procedure system. Firstly, it analyzes the relationship between the history and trajectory of the judicial case, and also the role of the people involved in the dispute (escribano, juez, partes) with the idea of showing a close and mediator-justice, where the protagonist were justiciable. Secondly, it studies the strategies of the parties, which were expressed both in their narratives and in their acts, with the objetive of presenting a judicial "experience" built throughout the direct or indirect contact with the judicial institution, and its personal or collective use. Finally, the paper aims to investigate the juridical culture of justiciables in order to show the singularity of their context.